Farooq Abdullah, Kashmir's prodigal son : a biography - Sinha, Aditya (New Delhi : UBS Publishers' Distributors, 1996)
Biography of Farooq Abdullah, politician and former chief minister of Jammu and Kashmir.
Keywords: Politicians -- India -- Jammu and Kashmir -- Biography; Jammu and Kashmir (India) -- Politics and government